2015
DOI: 10.1371/journal.pone.0132735
|View full text |Cite
|
Sign up to set email alerts
|

Sizing the Problem of Improving Discovery and Access to NIH-Funded Data: A Preliminary Study

Abstract: ObjectiveThis study informs efforts to improve the discoverability of and access to biomedical datasets by providing a preliminary estimate of the number and type of datasets generated annually by research funded by the U.S. National Institutes of Health (NIH). It focuses on those datasets that are “invisible” or not deposited in a known repository.MethodsWe analyzed NIH-funded journal articles that were published in 2011, cited in PubMed and deposited in PubMed Central (PMC) to identify those that indicate da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Furthermore, Influenza and Other Respiratory Viruses also reported that the IRD database paper (5) was the #1 cited paper in the journal in 2014. In a survey of research articles that were published in 2011 and had received NIH funding, IRD was the 6th most frequently acknowledged repository for molecular data, behind only some of the major databases managed by the U.S. National Library of Medicine (6). In addition, the IRD website has been heavily used by researchers worldwide, with over 1300 usage sessions per week on average in 2015 as per Google Analytics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Influenza and Other Respiratory Viruses also reported that the IRD database paper (5) was the #1 cited paper in the journal in 2014. In a survey of research articles that were published in 2011 and had received NIH funding, IRD was the 6th most frequently acknowledged repository for molecular data, behind only some of the major databases managed by the U.S. National Library of Medicine (6). In addition, the IRD website has been heavily used by researchers worldwide, with over 1300 usage sessions per week on average in 2015 as per Google Analytics.…”
Section: Introductionmentioning
confidence: 99%
“…This discussion is relevant because the increasingly data-centric nature of biological discovery has resulted in calls for improved access to existing data (NIH et al . 2012; R ead et al . 2015; W ilkinson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our more modest aim here is to highlight lessons we learned while constructing FlyClockbase, hoping they will be useful as the biological community works towards finding more general solutions (NIH et al . 2012; R ead et al . 2015; W ilkinson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most biomedical datasets are not deposited in a particular biomedical repository rather contained in the article itself(13), how to identify whether biomedical research articles are producing certain kinds of data is not a trivial issue. Like the biological processes and mechanisms being studied, the resulting data is diverse and the terminology describing the data reflects this diversity.…”
Section: Introductionmentioning
confidence: 99%